2018
DOI: 10.1186/s40168-017-0385-0
|View full text |Cite
|
Sign up to set email alerts
|

The association between anterior nares and nasopharyngeal microbiota in infants hospitalized for bronchiolitis

Abstract: BackgroundThe airway microbiome is a subject of great interest for the study of respiratory disease. Anterior nare samples are more accessible than samples from deeper within the nasopharynx. However, the correlation between the microbiota found in the anterior nares and the microbiota found within the nasopharynx is unknown. We assessed the anterior nares and nasopharyngeal microbiota to determine (1) the relation of the microbiota from these two upper airway sites and (2) if associations were maintained betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
67
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 59 publications
(73 citation statements)
references
References 55 publications
6
67
0
Order By: Relevance
“…Furthermore, compared to healthcare worker‐collected NPS from children during ARI episodes, we have observed similar yields by PCR of H. influenzae , and higher yields of S. pneumoniae and M. catarrhalis , from parent‐collected anterior nasal swabs mailed into the laboratory (Lambert, unpublished RESPECT data; http://clinicaltrials.gov: NCT00966069). In addition, a recent 16S rDNA sequencing study in hospitalized infants with bronchiolitis found good within‐individual correlations between Haemophilus and Moraxella in nasopharyngeal aspirate and mailed nasal swab specimens . Finally, while the oropharynx rather than nasopharynx has been suggested as the optimal sampling site for H. influenzae , this observation may be biased by inadequate differentiation between H. influenzae and H. haemolyticus , the latter being common in the oropharynx …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, compared to healthcare worker‐collected NPS from children during ARI episodes, we have observed similar yields by PCR of H. influenzae , and higher yields of S. pneumoniae and M. catarrhalis , from parent‐collected anterior nasal swabs mailed into the laboratory (Lambert, unpublished RESPECT data; http://clinicaltrials.gov: NCT00966069). In addition, a recent 16S rDNA sequencing study in hospitalized infants with bronchiolitis found good within‐individual correlations between Haemophilus and Moraxella in nasopharyngeal aspirate and mailed nasal swab specimens . Finally, while the oropharynx rather than nasopharynx has been suggested as the optimal sampling site for H. influenzae , this observation may be biased by inadequate differentiation between H. influenzae and H. haemolyticus , the latter being common in the oropharynx …”
Section: Discussionmentioning
confidence: 99%
“…All site researchers collected nasopharyngeal aspirates (NPAs) within 24 hours of hospitalization by using the same equipment (eg, sample traps and suction catheters from Medline Industries [Mundelein, Ill]) and a standardized protocol, as previously described. 15…”
Section: Nasopharyngeal Aspirate Collectionmentioning
confidence: 99%
“…Within 24 hours of hospitalization, site teams collected an index nasal swab from both anterior nares by using a single nylon pediatric FLOQSwab (Copan, Brescia, Italy). 15 This swab was collected either before the NPA collection or more than 2 hours after the NPA collection. During hospitalization, site teams taught parents how to collect the nasal swab sample.…”
Section: Nasal Swab Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Future research could focus on which child with bronchiolitis is likely to relapse and require hospitalization (or re‐hospitalization) and will require greater use of health‐care resources . We only explored biomarkers along the inflammatory and apoptotic pathways in our study, but the anterior nares may also contain microbial risk markers that may prove useful in bronchiolitis . These should be explored in the search for an objective predictive tool in bronchiolitis.…”
Section: Discussionmentioning
confidence: 99%